Comparison of Missing Permanent Tooth in Bangladeshi Unilateral Cleft Lip and Palate to those without Cleft Lip and Palate (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: The distribution of dental abnormalities specially missing tooth is common among the cleft palate & lip patient wherefore the aim of this study was to evaluate the prevalence of hypodontia in case of Bangladeshi cleft population.Objective: The purpose of the present study was to compare the congenital tooth deficiencies seen in permanent dentition in individuals with unilateral cleft lip and palate (UCLP) to non-cleft individuals with Angle Class I malocclusion.Methodology: This is a retrospective case control study between UCLP and Angle Class l malocclusion patients. This study was done on OPG films taken before treatment from 80 patients who applied for orthodontic treatment. 40 individuals with UCLP between the ages of 12 - 16 years were compared with the 40 individuals with Angle Class I malocclusion with no CLP aged between 12 - 16 years. Individuals with UCLP; 21 clefts were on the left side and 19 clefts were on the right side. The congenitally deficient teeth were recorded from the OPG films. In this study, third molars were not included in the evaluation.Results: In this study, no differences were found in regard to the gender of the patient. The left side of the patients was affected substantially more than the right side. The frequency of the missing upper lateral incisors in the cleft side of the patients was significantly higher than the non-cleft side. Therapists of cleft patients need to be aware of the high variety of numerical alterations, as this is important for therapy planning and the applied treatment.Conclusion: The management of dental anomalies, which can easily be detected by careful inspection of routine orthodontic diagnostic records, should be taken into consideration in treatment planning of individuals with a cleft.Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):198-201